(untitled) (Pedagogy of Higher and Secondary Education, 2021)
The article contains analysis of basic approaches to forming the problem of professional competemcy of students. It touches upon pedagogical and psychological approaches to solving the stated problem. Also it examines the components of professional competency of students.